Potential Risk of Contamination of the Dunas-Barreiras Aquifer System by Anthropic Activities in a Source Area in Northeastern Brazil - Bezerra, Allison Vicente Silva; de Castro, Vera Lúcia Lopes; Di Lollo, José Augusto [UNESP]; Lorandi, Reinaldo; Costa, Carlos Wilmer (My University, 2023)
The Dunas-Barreiras Aquifer system is in the NE region of Brazil, near the eastern coast of Rio Grande do Norte, and in it, one finds the Bonfim Lake System. Such aquifer is used for the supply of about 300,000 people, is characterized as free and is composed of a single system, although the dunes and the Barreiras Formation have specific characteristics. From a Multicriterion Analysis, involving maps algebra and Weighted Linear Combination of physical, biotic and anthropic attributes, in Geographic Information Systems (GIS) environment, the present work proposes to identify, in 1:100.000 scale, areas with higher potential risks of groundwater contamination in the area covered by the Bonfim System. The results point that 46.14% of the spring presented contamination potentials Medium, Strong and Very Strong. On the other hand, areas with despicable potential covered 39,73% represented by semi-natural areas, without the presence of anthropic activities. The spatialization of the potential risk of contamination of the underground water of this spring aims to help in the decision making, public and private, contributing for the territorial planning of the municipalities of São José de Mipibu and Nísia Floresta, presenting areas in which the anthropic use should be delayed, prioritizing the conservation.
Potencial Risco de Contaminação do Sistema Aquífero Dunas-Barreiras por Atividades Antrópicas em Área de Manancial no Nordeste brasileiro
Keywords: Anthropic activities; Environmental modeling; GIS; Groundwater Contamination; Land use and land cover; Multicriteria analysis